2006
DOI: 10.1111/j.1439-0531.2006.00666.x
|View full text |Cite
|
Sign up to set email alerts
|

Comparison between Cloprostenol‐induced and Spontaneous Oestrus Fertility in Dairy Cows

Abstract: ContentsA short calving to conception interval is of main importance to achieve high economic efficiency in dairy cow industry. In order to reduce this interval, several hormonal treatments have been put on the market, in which cloprostenol, a synthetic analogue of prostaglandin F 2a (PGF 2a ). The aim of this study was to compare fertility of cloprostenol-induced oestrus to that of spontaneous oestrus in dairy cows. In a group of 525 cows, 280 (treated group) were administered 0.5 mg cloprostenol i.m. after … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
13
0
2

Year Published

2009
2009
2015
2015

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(16 citation statements)
references
References 31 publications
1
13
0
2
Order By: Relevance
“…In other studies, the accuracy of rectal palpation for the presence of a functional CL was 73.9%, which confirms the unreliability of rectal palpation alone to assess the functionality of the CL (Cairoli et al, 2006).…”
Section: Acta Veterinariasupporting
confidence: 48%
See 1 more Smart Citation
“…In other studies, the accuracy of rectal palpation for the presence of a functional CL was 73.9%, which confirms the unreliability of rectal palpation alone to assess the functionality of the CL (Cairoli et al, 2006).…”
Section: Acta Veterinariasupporting
confidence: 48%
“…In contrast, other studies concluded that both products were equally effective luteolysins and produced similar pregnancy outcomes in lactating dairy cows (Stevenson and Phatak, 2010). Cairoli et al (2006) found no differences in conception rates between cloprostenol and dinoprost in cows inseminated at observed oestrus. In agreement with the findings of the present study, Salverson et al (2002) reported that following administration of PGF 2α (dinoprost and racemic cloprostenol) in combination with MGA, the oestrus synchronisation and fertility results were similar for the two prostaglandins.…”
Section: Discussionmentioning
confidence: 42%
“…Several studies have also indicated that the fertility (conception and calving rates) of aPGF2α synchronized cows is comparable to that of cows exhibiting spontaneous estrus [34,35]. However, Diskin et al [18] suggested that the inconsistent results between studies is attributable to differences in management conditions, cow physiological and pathological status, and estrus detection efficiency and accuracy.…”
Section: Pharmacological Synchronization Of Estrusmentioning
confidence: 99%
“…Moreover, the stage of the estrous cycle at the time of aPGF2α injection can affect fertility synchronization [22]. Therefore, this highlights the importance of establishing the ovarian status in early postpartum dairy cows before initiation of an artificial insemination protocol in terms of the luteal activity and synchronization protocols [24,32,33].Several studies have also indicated that the fertility (conception and calving rates) of aPGF2α synchronized cows is comparable to that of cows exhibiting spontaneous estrus [34,35]. However, Diskin et al [18] suggested that the inconsistent results between studies is attributable to differences in management conditions, cow physiological and pathological status, and estrus detection efficiency and accuracy.…”
mentioning
confidence: 99%
“…The distribution of days from enrollments until detection of estrus is presented in Figure 2. In a similar study, estrus was observed in 82% of the cows within 7 d of PGF 2a administration diagnosed with a CL via rectal palpation (Cairoli et al 2006). Estrus, found by visual observation and tail chalk evaluation after morning milking, was detected in 75% of cows given PGF 2a at non-pregnant diagnosis (Stevenson et al 2003).…”
Section: Resultsmentioning
confidence: 93%